Enhancement of material attributes of poorly compressible metformin hydrochloride through coprocessing with hydroxypropyl cellulose (HPC-L) using coprecipitation (CPT) - Kaushalendra Chaturvedi; Pasaorn Pongkulapa; Xiaoyi Ding; Harsh S. Shah; San Kiang; Veeran Kadajji (SpringerOpen, 2023)
Abstract Coprocessing involves integration of multiple substances to improve the physical, chemical, mechanical, and biopharmaceutical properties of a material. Coprocessing is a promising technique in the pharmaceutical industry which support both drug substance and drug product processes. When active pharmaceutical ingredients (APIs) are coprocessed with excipients, it can enable direct compression and continuous manufacturing. Hydroxypropyl cellulose (HPC-L), a commonly used excipient in pharmaceutical formulations, can enhance drug stability, solubility, and bioavailability. In this study, we have employed coprecipitation (CPT) to coprocess metformin hydrochloride (MET) with HPC-L, resulting in the formation of agglomerates with improved physical attributes without any risk of polymorphic changes. Acetone/acetonitrile and heptane were used as solvent and antisolvent, respectively. Screening study revealed that the use of a rotor stator helps to control the size of metformin hydrochloride and HPC-L agglomerates (M-CPT) without negatively impacting bulk density and powder flow properties. The CPT agglomerates showed residual solvent levels within the specified ICH limits. Powder rheology results demonstrated a sixfold increase in FFC of M-CPT compared to neat MET. The compressibility, tabletability, compactability, and "In-Die" Heckel analysis data further suggested that the M-CPT agglomerates are directly compressible with no observable changes in the dissolution profile of MET. Overall, this study demonstrates application of CPT approach to tune the physical and mechanical properties, and HPC-L can be used as an excipient of choice for CPT technique to improve the compressibility and flowability of APIs. Graphical Abstract